IDENTIFIKASI TANAMAN KANTONG SEMAR (Nepenthes sp.) TERKAIT FENOLOGINYA PADA DAERAH TERBUKA (PANAS) DI KAWASAN BUMI PERKEMAHAN SOBLEMAN WILAYAH RESORT WONOLELO, TAMAN NASIONAL GUNUNG MERBABU - Bebi Sylvia Muryanto; Danastri Nur Athaya Radya Putri (Yayasan Nusantara Hasana Berdikari, 2023)
Pitcher plants (Nepenthes sp.) grow well in the Sobleman Campground area located in the Wonolelo Resort area. Pitcher plants that grow at an altitude of 1,682 meters above sea level (the highest) with the lowest temperature of 22.8 and humidity of 83.5 Rh have the highest growth rate characterized by the highest number of pockets and long and branched plant stems so that they grow higher. Pitcher plants located at an altitude above 1,665 meters above sea level are also found flowering with brown flowers. It is also known from observations, the higher the location, the higher the level of solar irradiation because it is not blocked by the plant header. This study shows that altitude, temperature, humidity, and the level of solar irradiation will affect the growth of pitcher plants. This study aims to determine the growth of pitcher plants in terms of phenology and anthropological factors that influence it.